Stabilitas Ekonomi Makro dan Imbal Hasil (Yield) Obligasi Pemerintah di Negara ASEAN-5 - Tetuko Rawidyo Putro; Riwi Sumantyo; Hery Sulistio Jati NS; Andri Prasetyo; Muhammad Gilang Gumilar (Jurnal Ekonomi-Qu, 2022)
This research is about differences in yields of government bonds in 5 ASEAN countries. The differences in economic conditions between countries are expected to be considered by investors in entering the number of funds. The general objective of this study is to determine the effect of macroeconomic relationships on government bond yields. The specific aim of this study is to determine the differences in the macroeconomic impact of 5 ASEAN countries (Indonesia, Singapore, Malaysia, Thailand, and the Philippines) on government bond yields. This study uses panel data analysis. This study uses secondary data consisting of monthly data from government bond yields, exchange rates, inflation, and benchmark interest rates. The analysis found a significant negative effect of the exchange rate variable on the imbalance of results (yield). Meanwhile, macroeconomic indicators of inflation and interest rates have a positive and significant effect on unbalanced results. The analysis results show that there is no significant difference in the economic conditions of the ASEAN-5 countries on the yield of the 10-year government bonds.